Micro‐organisms growing on rapeseed during storage affect the profile of volatile compounds of virgin rapeseed oil. (1st November 2017) - Wagner, Claudia; Bonte, Anja; Brühl, Ludger; Niehaus, Karsten; Bednarz, Hanna; Matthäus, Bertrand
Abstract: BACKGROUND: Micro‐organisms populate on rapeseed after harvest during storage depending on the growing conditions. The composition of the bacterial colonization is unknown, although its contribution to the profile of volatile aroma‐active compounds determines the sensory quality of virgin cold‐pressed rapeseed oil. RESULTS: From four rapeseed samples, 46 bacterial strains were isolated. By DNA‐sequencing, the identification of four bacteria species and 17 bacteria genera was possible. In total, 22 strains were selected, based on their typical off‐flavors resembling those of virgin sensory bad cold‐pressed rapeseed oils. The cultivation of these strains on rapeseed meal agar and examination of volatile compounds by solid phase microextraction–gas chromatography–mass spectrometry allowed the identification of 29 different compounds, mainly degradation products of fatty acids such as alkanes, alkenes, aldehydes, ketones and alcohols and, in addition, sulfur‐containing compounds, including one terpene and three pyrazines. From these compounds, 19 are described as aroma‐active in the literature. CONCLUSION: Micro‐organisms populating on rapeseed during storage may strongly influence the sensory quality of virgin rapeseed oil as a result of the development of volatile aroma‐active metabolic products. It can be assumed that occurrence of off‐flavor of virgin rapeseed oils on the market are the result of metabolic degradation products produced by micro‐organisms populating on rapeseed during storage. © 2017 Society of Chemical Industry